Interactive map of cultural parks in Wietrzychowice and Sarnowo - Kulesza, Maja (Who needs tourism?, 2024)
This article outlines the subject of the Kuyavian megaliths located in the Kuyavian-Pomeranian region of Poland. The basic concepts were explained, the origin and history of the tombs were described. Then, the process of creating an interactive map of the megaliths located in the cultural parks in Wietrzychowice and Gaj Stolarski and in Sarnowo was presented. The StoryMaps application was created on this basis.